ANATOMICAL STUDY OF THE TRACHEAL CAST AND LUNG IN LOCAL BREED CATS Felis Cactus Domesticus.L. - Shakir Mahmood Mirhish Rabab Abd Alameer Nassar (Basrah Journal of Veterinary Research)
Cast technique includes ten cats (5 male, 5 female) used the polymerizing resin (cold acrylic) to study the bronchial tree and blood vessels. the examination of bronchial tree of the cats (felis catus) Lung is done by using cold resin in order to prepare cast specimens. The diameter of right principal bronchi of cats mean (7.34 mm± 0.36) and diameter of left principal bronchi means (6.07mm 0.36). The right principal bronchi large than left principal. The air flow in right Lung faster than the left. This result is supported by the researcher .These results are obtained from the cast model showing that the pulmonary trunk divides into right and left pulmonary arteries after arising from the right ventricle of heart. The right pulmonary artery the diameter about (4.18 mm) and diameter of left pulmonary artery about (3.40 mm) that the right pulmonary larger than the left pulmonary artery